The altar apse frescoes in the church of Nativity of the Virgin in Betania (Georgia): painting style and question of dating - Makarova, Anna L. (Actual Problems of Theory and History of Art, 2012)
The paper presents some considerations regarding the date of the altar apse frescoes in the church of Nativity of the Virgin in Betania. The article also discusses the architecture of Betania church, in connection with a possible reconstruction of the church in the 12th century. Corroboration of this probable rebuilding can help us to define the dating of different parts of Betania wall painting. The altar apse frescoes of Betania are compared with a group of Georgian church frescoes relating to the reign of David IV the Builder (1073-1125). The author concludes that the available historical information and stylistic analysis confirm the dating of the altar apse frescoes of Betania to the end of the 11th - early 12th century.